An Autonomous Packet Transmission Strategy for Opportunistic Wireless Sensor Networks - Hakki Soy; Özgür Özdemir; Mehmet Bayrak (International Journal of Distributed Sensor Networks)
We consider a wireless sensor network that comprises a single hop between the sensor nodes and the central controller node with multiple antennas. In this system model, we concentrate on the single-beam opportunistic communication and propose two novel packet transmission schemes that can perform multiuser diversity gain based on the signal-to-noise ratio (SNR) and the normalized SNR (NSNR) measurements at the sensor nodes with single antenna. The main objective of the multiuser diversity is to increase the total throughput over the fast fading channels. Proposed schemes are based on the principle of cross-layer design that integrates with physical layer characteristics of wireless channel and medium access control (MAC) layer characteristics of network. In our design, we assume that the sensor nodes know only their own channels to the controller node and the packet transfer from the sensor nodes to the controller node is initiated when the channel quality of any node exceeds the predefined threshold at the current time slot. To determine the optimum threshold, we maximize the probability of successful packet transmission where only one sensor node transmits its packet in one time slot under the simplified collision model. Simulation results are demonstrated to compare the performance of the proposed schemes in terms of throughput, energy efficiency, and fairness. The obtained results show that the presented opportunistic strategy can be used to improve the network throughput.